Bienestar Animal. - Broom, Donald M.; De Fontenay, Elisabeth; Broberg, Birte; Merminod,Jacques; Kolar,Roman; Laroche,Charles; Gjerris, Mickey; Oláon, Anna.; Sandoe, Peter; Steiger, Andreas; Chevaáut,Daniel; Pietro Faggioni, Hermano Maurizio; et al. (Zaragoza (España) : Acribia S.A, 2007)
(Es)
188 ref.
Keywords: DERECHO ANIMAL